Comparison of bispectral index scores from the standard frontal sensor position with those from an alternative mandibular position - Lee, Shin Young (The Korean Society of Anesthesiologists, 2014)
BACKGROUND: The standard bifrontal application of the bispectral index (BIS) sensor interferes with the operative field in neurosurgery and plastic surgery. The aim of this study was to compare the standard frontal BIS sensor position with an alternative position across the mandible. METHODS: Two BIS™ Quatro sensors (Aspect Medical Systems, Newton, MA, USA) mounted on the frontal and mandibular regions were connected to BIS Vista™ monitors on each patient during general anesthesia. Data from each position were collected at awake, loss of consciousness, intubation, incision, every 30 minutes during the intraoperative period and emergence. These data were compared using Bland-Altman and scatter plot analyses. RESULTS: Scatter plot analysis revealed a significant correlation between BIS values of frontal and mandibular positions (R = 0.869, P = 0.000), except during emergence (R = 0.253, P = 0.077). Bland-Altman analysis revealed a negative bias of 3.2 with a limit of agreement of 16.5/-22.9, in which 3.7% of the values were outside of the limit of agreement. Additional values included -2.9 (14.1/-8.3) while patients were awake, -21.7 (14.9/-58.3) at loss of consciousness, -1.8 (9.0/-12.5) during maintenance, and -1.9 (14.9/-18.8) during emergence. CONCLUSIONS: Overall, BIS values do not agree between the standard frontal position and an alternative mandibular position. However, during the anesthesia maintenance period, the mandibular position can be availably used as an alternative position if the operative field renders the standard frontal position unavailable.